Assessment of the consequences of the destruction of the Kakhovska HPP dam on irrigated lands in the zone of influence of the Kakhovsky water reservoir - Dorosh, Y.; Ibatullin, Sh.; Dorosh, O.; Sakal, О.; Dorosh, А.; Tarasenko, А. (Land Management, Cadastre and Land Monitoring, 2024)
According to preliminary estimates by scientists of the Institute of Land Use of the National Academy of Sciences, it was established that the area of irrigated agricultural land, which is in the zone of influence of the Kakhovsky Reservoir, including the occupied territories, amounted to 1,267.8 thousand hectares, of which about 500 thousand hectares had potential irrigation. The need for a more detailed study of the spatial identification of irrigated lands has been proven. The area of irrigated land in the area of influence of the Kakhovsky Reservoir was clarified by spatial comparison and digitization of: irrigation schemes, boundaries of land plots, boundaries of irrigated fields according to indices of vegetation and soil moisture using GIS technologies and remote sensing of the Earth. This makes it possible to calculate the area of agricultural land, the irrigation of which will be complicated due to the destruction of the dam of the Kakhovska HPP and changes in the Kakhovsky reservoir. In the future, it is important to determine and evaluate the impact of hostilities and other negative phenomena of armed aggression in this region on land use and infrastructure.Based on a preliminary analysis of hydrography and water channels, the scientists of the Institute of Land Use of the National Academy of Sciences of the Russian Academy of Sciences determined administrative districts whose land irrigation depended on the Kakhovsky Reservoir.It is proposed to introduce the accounting of reclaimed land, as well as land affected by hostilities in the cadastre.We believe that monitoring of irrigated and drained lands, and lands that will be returned to circulation after the elimination of the effects of hostilities, should be an element of land monitoring.
Keywords: Kakhovska HPP; the zone of influence of the Kakhovska Reservoir; reclaimed lands; irrigated lands; occupied territories; geo-information technologies; monitoring of irrigated and drained lands; artificial intelligence